(untitled) (Tempo e Argumento, 2022)
This article aims to analyze the Brazilian indigenous question during the central years of the military dictatorship from a transnational perspective. This approach emphasizes historical phenomena based on people and ideas, emancipating them from nation-states as a "natural" framework for the study of history. The first part of this text discusses the importance of public opinion in international relations to subsequently understand how the Brazilian state faced foreign interference in issues that the rulers of the dictatorial period believed to be of national competence. Subsequently, from the reflection about the symbolic power of indigenous peoples in Brazil and abroad, an analysis will be made in two parts: in the first, a case study focused on the impact that the Figueiredo Report – upon its international release – had in France; then, we will extend to the transnational sphere our observations on the damage caused by the denunciations contained in the aforementioned report, seeking to find the communicating vessels between what was happening in Brazil, its reading by international public opinion, the ways in which the military authorities acted to protect the country’s external image, and also the possible advantages obtained by national actors who, in the 1970s, were acting in favor of the indigenous cause. Keywords: indigenous people; military dictatorship; transnational history; public opinion; international relations.